FINANCIAL LITERACY, DEMOGRAPHIC FACTORS, OVERCONFIDENCE, AND INVESTMENT DECISIONS AMONG UNIVERSITY STUDENTS IN INDONESIA'S MAJOR CITIES - Malini, Helma (Berkala Akuntansi dan Keuangan Indonesia, 2025)
This study aims to examine the influence of financial literacy, gender, age, income, ethnicity, and semester on overconfidence and investment decisions among university students in three major cities in Indonesia (Jakarta, Bandung, and Surabaya). It also investigates the role of overconfidence as a mediating variable in the relationship between these factors and investment decisions. This research uses a quantitative approach with an associative research design. The population includes all university students in Jakarta, Bandung, and Surabaya who have invested in stocks. A sample of 100 respondents was selected using purposive sampling, with criteria that respondents must be university students (from both public and private universities in these cities) who have not graduated, are listed stock investors in the Indonesia Stock Exchange, are at least 18 years old, and have been investing in the stock market for a minimum of one year. The results show that financial literacy, income, and semester positively influence overconfidence, while gender, age, and ethnicity do not. Financial literacy positively influences investment decisions, whereas gender, age, income, ethnicity, and semester do not. Overconfidence positively influences investment decisions. Financial literacy impacts investment decisions with overconfidence as a mediating variable, while gender, age, income, ethnicity, and semester do not have such an influence through overconfidence